2016
DOI: 10.4103/2008-7802.190091
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use and substance abuse in students of Karaj Universities

Abstract: Background:It is clear that tobacco smoking and substance abuse have negative consequences on adolescent and youth's health. Tobacco smoking especially hookah smoking has increased worldwide especially among university students. This study aimed to determine the prevalence of risk-taking behaviors such as cigarette smoking, hookah smoking, alcohol use, and drug abuse and its predictors in students of Karaj universities.Methods:This cross-sectional study took place in Karaj in January and February 2014. The ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
3
8
1
1
Order By: Relevance
“…Investigations revealed that the frequency of waterpipe consumption among Iranian students was reported differently. Frequency of waterpipe consumption in our study is significantly lower than the results of the research conducted on the students of state universities in Tehran (40.3%) [12] and Karaj (51.2%) [13], but similar to the consumption frequency (29%) reported in the research conducted by Dehdari et al [7]. The frequency of waterpipe consumption in two studies conducted by Rezakhani Moghadam [14] (23.3%) and Taremian [15] (25.7%) on students of medical universities of Tehran and the study conducted by Rahimzadeh [11] on physical education students of Kurdistan University (24.7%) has been reported less than that of the current research.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Investigations revealed that the frequency of waterpipe consumption among Iranian students was reported differently. Frequency of waterpipe consumption in our study is significantly lower than the results of the research conducted on the students of state universities in Tehran (40.3%) [12] and Karaj (51.2%) [13], but similar to the consumption frequency (29%) reported in the research conducted by Dehdari et al [7]. The frequency of waterpipe consumption in two studies conducted by Rezakhani Moghadam [14] (23.3%) and Taremian [15] (25.7%) on students of medical universities of Tehran and the study conducted by Rahimzadeh [11] on physical education students of Kurdistan University (24.7%) has been reported less than that of the current research.…”
Section: Discussioncontrasting
confidence: 90%
“…One of the most influential factors encouraging students to consume waterpipe was friends who had a history of waterpipe consumption. This result was also reported in the research conducted by TaragiJah et al [12] in students of public universities and Kabir et al [13] among the students of Karaj University. In general, having friends with a history of waterpipe consumption is a risk factor for waterpipe consumption, and it is effective in encouraging students to consume it [26].…”
Section: Discussionsupporting
confidence: 87%
“…The studied adolescents reported they had family members who smoke inside and outside the home and members who use other drugs. A study showed that adolescents who have parents or friends who smoke are more likely to try smoking than those who do not have parents or friends who smoke (2) . This finding reveals that adolescents are influenced by their loved ones to start smoking inside the home.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that the prevalence of smoking among adolescent students is 9.3% (2) . The National School Health Survey showed that public school students (19.4%) stated they had experimented smoking with more intensity than private school students (12.6%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation